Razão e sensibilidade: a idéia de espírito no confronto entre estoicismo e hedonismo moderno na fenomenologia do espírito - Bruno Rafael Camargos de Oliveira (2013)
The goal of this dissertation is to discuss the definition of human being by confronting two figures of consciousness in Hegel's Phenomenology of Spirit. The first figure, Stoicism, in its truth, neglects the feeling in favor of a pure thought. The second, modern hedonism, is represented by the figure "pleasure and necessity" that, in its truth, neglects rational thought in favor of feelings and pleasures. In the confrontation of these two figures, which are part of the experience of consciousness, we point out the efficiencies and deficiencies of each one in order to understand the truth that they say or contribute to the definition of human being. In order to do this, we start the research with the analysis of the concept of "experience" while also addressing the concepts that tangent it. Because it is a broad concept in the Phenomenology of Spirit, the investigation of the definition of experience helps us understand and explain the one-sidedness of the both figures. Being a research in the field of philosophical anthropology, briefly we explore the concept of spirit, a fundamental one in the work of Hegel, and it is interpreted as the absolute manifested in the human subject, which is finite. So while each figure says that what is partially human, we close the research by waving at an idea of merging these two figures in order to answer the question of the definition of human being, without, however, exhausting it.